2022
DOI: 10.1039/d2ra04455b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a porous SiO2–H3BO3–V2O5–P2O5 glassy composite: structural and surface morphological behaviour for CO2 gas sensing applications

Abstract: The present work mainly focuses on the fabrication of a porous glass 40SiO2–35H3BO3–19V2O5–6P2O5via a melt-quenching technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…By investigating how sensors respond to various gases, these studies contribute to enhanced selectivity, reliability, and overall performance, which are crucial for gas sensor applications. 57 In our work, the developed CZO-based sensing materials have demonstrated high selectivity properties upon consecutive exposure (CO 2 , CO, and CH 4 ) and when exposed to a mixture of CO 2 and acetone (see Figure 8 c,d). It was observed that certain gases influenced the resistance background level, potentially indicating low desorption.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…By investigating how sensors respond to various gases, these studies contribute to enhanced selectivity, reliability, and overall performance, which are crucial for gas sensor applications. 57 In our work, the developed CZO-based sensing materials have demonstrated high selectivity properties upon consecutive exposure (CO 2 , CO, and CH 4 ) and when exposed to a mixture of CO 2 and acetone (see Figure 8 c,d). It was observed that certain gases influenced the resistance background level, potentially indicating low desorption.…”
Section: Resultsmentioning
confidence: 62%
“…Cross-sensitivity studies are pivotal in gas sensor development to ensure improved specificity and accuracy. By investigating how sensors respond to various gases, these studies contribute to enhanced selectivity, reliability, and overall performance, which are crucial for gas sensor applications . In our work, the developed CZO-based sensing materials have demonstrated high selectivity properties upon consecutive exposure (CO 2 , CO, and CH 4 ) and when exposed to a mixture of CO 2 and acetone (see Figure c,d).…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 on dissociation produces carbonic acid ions (HCO 3 ̅ ) that are acidic, whereas NH 3 dissociation forms ammonium ions (NH 4 + ) that are basic in nature. The adsorption/desorption of these charged species influences the electrical resistance of the PDMD sensor. …”
Section: Resultsmentioning
confidence: 99%
“…The sensing device, utilized for evaluating electrical resistance which is connected to the computer system through the Keithley electrometer (6517B). All the measurements were conducted at ambient temperature (32 °C and 60% RH) [30]. Figure 1 illustrates a schematic representation of the CO 2 gas sensing setup.…”
Section: Device Fabrication and Measurementsmentioning
confidence: 99%